(untitled) (Tanzania Medical Journal, 2010)
Reports on anatomical variations and anomalies are very important in keeping track of changes that occur in the human body during development. Not only does it help to explain some of the disease conditions affecting people, but it can aid in describing the aetiology of some of these conditions. The current observation indicated the presence of unusual bilateral foramina in the middle cranial fossa communicating with the sphenoid air sinuses. They were located anterolateral to the sella turcica and medial to the superior orbital fissure behind the optic canal. The complexity of sphenoid bone development and non fusion of some of its parts may lead to abnormal foramina like the ones seen in this case. Since observations were made on a prepared dried skull, the contents ofthe foramina were not verified. Another observation in the same skull was the bilateral abnormally joined anterior and posterior clinoid processes. The two were joined by a thick bar of bone (Interclinoid bar). Any outgrowth from the posterior clinoid process may compress the surrounding neuro-vascular structures especially the internal carotid artery. In the present case, the clinical history of the patient was not available to corroborate this observation. Knowledge on the described abnormalities of this skull may be useful for radiologists, neurosurgeons, endocrinologists as well as anthropologists.Key words: Middle cranial fossa, bilateral foramina, Sphenoid sinuses